PROFITABILITAS USAHA PETERNAKAN AYAM BROILER DENGAN TIPE KANDANG YANG BERBEDA - Nurul Mukminah; Rita Purwasih (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
This study aims to determine and compare the profitability of different types of broiler chicken farms (open and cloused houses) in Subang Regency. This study involved 9 farmers consisting of 5 farmers with closed house and 4 farmers with open house who partnered with PT. Surya Unggas Mandiri (PT. SUM). Production costs taken are 2 production periods from May-August 2018. Data are analyzed using economic analysis and descriptive methods. The results showed that the production cost per period per 1000 birds closed house was higher (Rp. 27.656.768,-) compared to open house (Rp. 24.975.671,-). The revenue per period per 1000 birds of closed house is higher (Rp. 30.606.931,-) compared to open house (Rp. 25.788.618,-). The profit of farmers who use closed house is higher (Rp. 2.621/period/bird) than open house (Rp.417,-). The profitability in close house s is 9.48% and is very feasible to develop